Prevalensi dan Faktor Risiko Penyakit Maag pada Masyarakat di Kelurahan Jayaloka Empat Lawang - Susanty, Leni; Syarah, Nilai; Yuliana, Jerri; Asmarini, Yetty; Aprianti, Delta; Rohani, Tuti; Azissah, Danur (Jurnal Gotong Royong, 2025)
Peptic ulcer disease (gastritis) is one of the gastrointestinal diseases commonly found in Indonesia, including in the Jayaloka Village area, Empat Lawang. Factors such as diet, smoking habits, alcohol consumption, and stress levels can influence the prevalence of this disease. This study aims to determine the prevalence and risk factors of peptic ulcer disease in Jayaloka Village with 50 respondents.Methods: This study used a cross-sectional design with 50 randomly selected respondents from Jayaloka Village. Data were collected through a questionnaire covering information on diet, smoking habits, alcohol consumption, stress levels, and symptoms of peptic ulcer disease. Data were analyzed descriptively and inferentially using the chi-square test to identify significant relationships between risk factors and the prevalence of peptic ulcer disease.Results: The results showed that the prevalence of peptic ulcer disease in Jayaloka Village was quite high, with significant risk factors found between unhealthy diet, smoking habits, alcohol consumption, and stress levels. Most respondents who suffered from peptic ulcer disease reported having irregular eating habits and high stress levels.Conclusion: Peptic ulcer disease has a significant prevalence in Jayaloka Village, with unhealthy diet, smoking habits, alcohol consumption, and stress levels as the main risk factors. This study provides a foundation for designing more effective public health programs in the prevention and management of peptic ulcer disease in the area.